2010
DOI: 10.1097/shk.0b013e3181dc0845
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Activation Differentially Mediates the Host Response to Sepsis

Abstract: Survival during sepsis requires both swift control of infectious organisms and tight regulation of the associated inflammatory response. As the role of T cells in sepsis is somewhat controversial, we examined the impact of increasing antigen-dependent activation of CD4 T cells in a murine model of cecal ligation and puncture using T-cell receptor transgenic II (OT-II) mice that are specific for chicken ovalbumin (OVA) in the context of major histocompatibility complex II. Here, we injected OT-II mice with 0, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 43 publications
5
39
0
1
Order By: Relevance
“…The suggestion of early cross talk between the innate and adaptive immune responses extends from recent reports, indicating the necessity of T cells in bacterial clearance following infection (29,37,54,55). Additionally, T-cell activation was newly linked to bacterial clearance through increased neutrophil oxidative burst and phagocytosis (29).…”
mentioning
confidence: 63%
“…The suggestion of early cross talk between the innate and adaptive immune responses extends from recent reports, indicating the necessity of T cells in bacterial clearance following infection (29,37,54,55). Additionally, T-cell activation was newly linked to bacterial clearance through increased neutrophil oxidative burst and phagocytosis (29).…”
mentioning
confidence: 63%
“…It is also argued that this epitope also bears at least one B cell epitope (323)(324)(325)(326)(327)(328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339), however, there is only one study that has mentioned the presence of the B cell epitope [327]. In a study by Sun et al, it was shown that 50% of the B cell response generated by the OVA protein was antibody specific to the OVA323-339 epitope [327].…”
Section: Immunisation By Mannosylated Peptides Resulted In An Impairementioning
confidence: 99%
“…In a study by Sun et al, it was shown that 50% of the B cell response generated by the OVA protein was antibody specific to the OVA323-339 epitope [327]. As the vaccine structures (G1-6) contain the CD4 epitope (OVA [323][324][325][326][327][328][329][330][331][332][333][334][335][336][337][338][339], the in vivo ability of vaccine structures (G1-9) for a T cell activation proliferation was assessed. Here, OT-II proliferating cells are considered to be activated when T cells expressing CD45.2 increase in percentage over the total parental CD4 + T cells [329].…”
Section: Immunisation By Mannosylated Peptides Resulted In An Impairementioning
confidence: 99%
See 2 more Smart Citations